Assessing the responses of cellular proteins induced by hyaluronic acid-modified surfaces utilizing a mass spectrometry-based profiling system: Over-expression of CD36, CD44, CDK9, and PP2A - Yang, Ming-Hui; Jong, Shiang-Bin; Lu, Chi-Yu; Lin, Yu-Fen; Chiang, Pei-Wen; Tyan, Yu-Chang; Chung, Tze-Wen (Analyst (London), 2012)
The cell responses to biopolymer surface at the early adhesion stages can be critical for cell survival. The purpose of this research was to assess formation of hyaluronic acid (HA) biopolymer surface, the fibroblasts were used as an experimental model to evaluate the responses of cellular proteins induced by biopolymer materials using a mass spectrometry-based profiling system. Surfaces were covered by multi-walled carbon nanotubes (CNT), chitosan (CS), and HA to increase the surface area, enhance the adhesion of biopolymer and promote the rate of cell proliferation. The amount of adhered fibroblasts on CNT/CS/HA electrodes of quartz crystal microbalance (QCM) were greatly exceeded those on other surfaces that were consistent with cell-count technique. Moreover, analyzing differential protein expressions of adhered fibroblasts on those biopolymer surfaces by proteomic approaches identified CD36, CD44, PP2A, and CDK9 as key proteins. To validate the influences of those four proteins on adhesions of fibroblasts on biopolymers, the cells were blocked by antibodies of the proteins and the adhesions of cells on the tested biopolymer surfaces were examined using a QCM technique, flow cytometric analysis and morphological observations. The results of significantly decreasing the weights and densities of the blocked fibroblasts adhering to CNT/CS/HA surfaces were obtained, and validate those proteins found by proteomic approaches. Utilizing mass spectrometry-based proteomics to evaluate cell adhesions on biopolymers is proposed.